Managerial behavior of sports facilities managers: an approach with public and non-profit organizations in São Paulo - Cacilda Mendes dos Santos Amaral; Leandro Carlos Mazzei; Flávia da Cunha Bastos; Rosiane Raduan Alexandrino (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: The sports facilities development and use optimization has been one of the main objectives of sports organizations. To understand how the management is performed, the knowledge about the manager and his function is crucial and may aid to improve facilities management and impact service quality. This study aimed to analyze the functional profile of sport facilities managers and verify their managerial behavior. Methods: A survey was conducted, 76 managers of public and non-profit sports facilities of São Paulo answering a questionnaire regarding their personal data and tasks performed in five related areas (Economic-Administrative Management, Human Resources Management, Maintenance, Supply and Exploration, and Marketing and Promotion). The data was analyzed through an Exploratory Factorial Analysis using the principal component method. Results: The low participation of managers in tasks related to the Economic-Administrative Management area was identified. The manager's other areas of activity had their tasks divided into the following factors: Human Resources (Work organization; Communication and Training); Maintenance (Maintenance and monitoring; Expansion, Construction, and Renovation); Supply and Exploration (Activities Organization; Activity Planning for Groups; Assignment and organization of use); Marketing (Communication, supply and demand analysis; Operation and occupation analysis). Conclusion: There is no standard managerial behavior of sport facilities managers since their performance is not focused on the proactive or non-proactive characteristic of the task, but rather on the field that the organization and/or manager deems necessary to be planned and developed.